Irrigation and fertilization on industrial tomato cultivation - Soares, José Monteiro; Faria, Clementino M. B. de (Pesquisa Agropecuaria Brasileira, 2014)
The influence of two irrigation methods two fertility levels and two fertilization systems on tomatoes, variety Rossol (VFN), were studied. The experimental design used was split-split-plot in rows with eight replicates. At harvest, classification on fruits, counting and weighting of commercial and noncommercial fruit (blossom-end-rot and rotten fruits) were done. For production of commercial fruits, significative difference was found at 5% and 1% levels for fertilization systems and interaction between fertilization and irrigation, respectively. Fertilization in furrows presented higher yield than in single spots when both systems were irrigated by sprinkling irrigation. For production of blossom-end rot infected fruits, significative differences were found for irrigation methods, fertility levels, fertilization systems and interactions. In the case of furrow irrigation, the production was higher when single spot fertilization was used. The plots irrigated by sprinkling irrigation presented the least percentage of blossom-end rot infected fruits.